The ECB and Euro-Area Enlargement - Berger, Helge (IMF Working Papers; Working Paper ;, 2002)
The likely enlargement of euro-area membership will radically change the environment under which monetary policy will be made in the euro area. Within less than a decade, the number of member countries in the euro area could more than double, with the vast majority of accession countries being relatively small in economic terms, compared with current members. Absent reforms, such a significant but asymmetric expansion could impede the effectiveness of the institutional policymaking process of the European Central Bank (ECB) and be seen by some as resulting in the overrepresentation of small member countries in the ECB Council. The paper illustrates these issues, describes the principles on which reforms of the ECB statute could build, and discusses four specific institutional reform scenarios. The analysis coincides with the ECB Council being scheduled to present suggestions for reform by late 2002.